Pregunta
upstudy study bank question image url

Apply all relevant properties of exponents to simplify the following expressions. Enter your answer as an integer or completely simplified fraction without exponents. a) \( (-8)^{-2} \) Answer b) \( \left(-\frac{1}{8}\right)^{-2} \) Answer c) \( -8^{-2} \) Answer d) \( -\left(\frac{1}{8}\right)^{-2} \) Answer

Ask by Wells Fleming. in the United States
Feb 26,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

a) 1/64 b) 64 c) –1/64 d) –64

Solución

We will simplify each expression step by step using the properties of exponents. a) (–8)⁻²  Step 1: Apply the negative exponent rule: a⁻ⁿ = 1/(aⁿ).  Step 2: Compute (–8)² = (–8) × (–8) = 64.  Thus, (–8)⁻² = 1/64. b) (–1/8)⁻²  Step 1: Again use the rule a⁻ⁿ = 1/(aⁿ).  Step 2: Compute (–1/8)². The square of a negative number becomes positive, so (–1/8)² = 1²/8² = 1/64.  Step 3: Therefore, (–1/8)⁻² = 1/(1/64) = 64. c) –8⁻²  Note: Here the exponent applies only to 8 (not to –8); the expression is interpreted as –(8⁻²).  Step 1: Compute 8⁻² = 1/(8²) = 1/64.  Step 2: Include the negative sign: –(1/64) = –1/64. d) –((1/8)⁻²)  Step 1: Compute (1/8)⁻². Using a⁻ⁿ form, (1/8)⁻² = 8² = 64.  Step 2: Now apply the negative sign: –64. Thus, the completely simplified answers are: a) 1/64 b) 64 c) –1/64 d) –64

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Bonus Knowledge

To simplify the given expressions using properties of exponents: a) \( (-8)^{-2} \) When simplifying this, remember that a negative exponent indicates the reciprocal, so: \[ (-8)^{-2} = \frac{1}{(-8)^2} = \frac{1}{64} \] **Answer:** \( \frac{1}{64} \) b) \( \left(-\frac{1}{8}\right)^{-2} \) Again, apply the negative exponent rule: \[ \left(-\frac{1}{8}\right)^{-2} = \frac{1}{\left(-\frac{1}{8}\right)^2} = \frac{1}{\frac{1}{64}} = 64 \] **Answer:** \( 64 \) c) \( -8^{-2} \) For this expression, first deal with the exponent: \[ -8^{-2} = -\frac{1}{8^2} = -\frac{1}{64} \] **Answer:** \( -\frac{1}{64} \) d) \( -\left(\frac{1}{8}\right)^{-2} \) Use the negative exponent rule here too: \[ -\left(\frac{1}{8}\right)^{-2} = -\frac{1}{\left(\frac{1}{8}\right)^2} = -\frac{1}{\frac{1}{64}} = -64 \] **Answer:** \( -64 \)

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad